Cognitive Aspects of Students in the Process of Learning to Read, Write, and Count in Lower Grades - Minsih, Minsih; Setiawan, Rio Jodi; Farhan, Novandra (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2025)
This study aims to identify various forms of cognitive impairment in elementary school students through a qualitative approach using a case study design. Data were collected through observation, in-depth interviews, and documentation of students, teachers, and parents in the school environment. The results of the study show that students' reading, writing, and arithmetic (calistung) impairments are present in mild symptoms of cognitive impairment such as dysgraphia (technical difficulty in writing) and mild dyscalculia (difficulty in understanding complex mathematical material). Students tend to find it easier to understand contextual material related to everyday life, while abstract material such as mathematics and foreign languages remain a challenge. The use of technology in learning has not become a common practice, with students preferring to search for information in books before turning to the internet. In addition, there were also indications of mild attention deficit and hyperactivity disorders in some students, which can affect the effectiveness of classroom learning. This study emphasizes the importance of learning strategies tailored to student needs, such as contextual methods, individualized approaches, and the use of technology as a supporting medium. These findings are expected to serve as a basis for schools in designing interventions that support optimal cognitive development in students and early detection of symptoms of cognitive disorders.